2016
DOI: 10.5935/0101-2800.20160073
|View full text |Cite
|
Sign up to set email alerts
|

Patient in chronic hemodialysis with right atrial mass: thrombus, fungal endocarditis or atrial myxoma?

Abstract: We present the case report of a 19-year-old patient with chronic kidney disease due to chronic glomerulonephritis, in hemodialysis (HD) by central catheter, with the incidental finding of a mass of 28x16 mm in right atrium (RA). The diagnosis of thrombus, infective endocarditis or myxoma were considered. Given the context of immunosuppression and difficult access vascular therapeutic practice has proved complex. Although Doppler echocardiography suggested thrombus in RA, nuclear magnetic resonance imaging (MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Our search produced a total of eight case series encompassing 32 cases and 32 additional individual case reports. 746 Same-patient CRAT recurrences were described in five reports 9,13,14,19,24 for a total of 68 cases of CRAT among 63 patients. Table 1 provides demographic details.…”
Section: Resultsmentioning
confidence: 98%
“…Our search produced a total of eight case series encompassing 32 cases and 32 additional individual case reports. 746 Same-patient CRAT recurrences were described in five reports 9,13,14,19,24 for a total of 68 cases of CRAT among 63 patients. Table 1 provides demographic details.…”
Section: Resultsmentioning
confidence: 98%
“…Subsequent echocardiographic identification of the catheter-attached fibrin-thrombin-cellular matrix or biomass is so common as to be considered generally benign. It is reported that portions of the fibrinthrombin biomass may remain adherent to the catheter or conversely may be sheared off and even remain in the venous system at the time of catheter removal through the skin [24][25][26]. As they are often identified in the subclavian veins, right atrium, superior vena cava (SVC) or right ventricle (RV), a knowledgeable echocardiographer will infer their presence and related etiology to a current or recently removed catheter [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…After 180 days of anticoagulation, there was significant reduction in mass. 14 RA thrombus is seen in 4% of patients diagnosed as PE and is associated with increased mortality. 15 Treatment options are controversial as there are limited data for comparison.…”
Section: Discussionmentioning
confidence: 99%